Tintinnids (Tintinnida: Ciliophora) from Colombia: An annotated distributional checklist - Sánchez, Daniela Rojas (Zootaxa, 2020)
Tintinnids are loricated ciliates found in coastal and oceanic waters that play a key role in the transference of energy to highest trophic levels. The purpose of this article is intended to integrate the available information about the taxonomy and distribution of Colombian tintinnids. An annotated distributional checklist based on published data is presented. One hundred and seven valid species of tintinnids, belonging to 12 families and 33 genera were listed. The genera Tintinnopsis and Eutinntinnus presented the highest number of species. Eighty-three species were recorded in the Caribbean basin and 51 in the Pacific, with a higher number in coastal waters.